If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(-4)-(-.8)=x
We simplify the equation to the form, which is simple to understand
(-4)-(-.8)=x
Remove unnecessary parentheses
-4-(-.8)=x
Remove unnecessary parentheses
-4 + 0.8=x
We move all terms containing x to the left and all other terms to the right.
-1x=+4-0.8
We simplify left and right side of the equation.
-1x=+3.2
We divide both sides of the equation by -01 to get x.
x=-3.2
| (x^2+6x-4)+(-x^2-6x+4)= | | 91+(-11)= | | 5y^2+y+1y=4 | | 3/x=5/2x | | 8z+33=3(3z+11)-z | | 89=x+13(7) | | 12x^2-(121/12)=0 | | -5(x-3)=10 | | -3(2x+2)=6x-8 | | 69=3(4x-1) | | 4x-1+2x-1=5y | | -5x-19=10 | | 15x+25y=120 | | 1y=3x-3 | | 915=10a-7 | | 5(3)-7=2(3+1) | | 94+27t=715 | | 5x-4(x+2)=29 | | =-4h+5j-4j+7h | | 5(x-3)=14 | | (2x)/7=2x^2 | | 5(2x-4)+7=12+3(2x+1) | | 816=24(v+12) | | 3)x-y)/5(2x/3y) | | -7(1+5x)=7(x+5) | | 120/350 | | 5y^2+4+1y=4 | | 2m^3+2m^2-24m= | | f(x)=164-16x | | W-15=0 | | 3/7•14 | | 48+54r=-15r |